Use of the partogram by doctors and midwives at Odi District Hospital, Gauteng, South Africa - Olga Maphasha; Indiran Govender; Pagollang D Motloba; Champak Barua (South African Family Practice)
Background: There is scientific evidence that using the partogram reduces maternal and foetal morbidity and mortality. The use of partograms by doctors and midwives at Odi District Hospital has been reported as inadequate by external audits. The level of knowledge of and use of partograms amongst doctors and midwives at Odi District Hospital was investigated.